Exploring Mothers Experiences on Complementary Feeding Practices Regarding Stunting Prevention - Tambunan, Evelyn Hemme (Jurnal Gema Keperawatan, 2023)
Complementary feeding is a significant milestone to promote childs healthy growth and development and prevent chronic malnutrition such as stunting. The aim of this study is to explore the mothers experience about complementary feeding practice regarding stunting prevention with children aged less than two years in Indonesia. A descriptive qualitative study was conducted from January to April 2023. This study was approved by Institutional Review Board (IRB) FIK UNAI. 22 mothers of children of 6-24 months of age were recruited by purposive technique form the mother who live in Cihanjuang Rahayu Village. Descriptive statistics were used to analyze the mothers demographic characteristics and thematic analysis was used to describe mothers experience about complementary feeding practices regarding stunting prevention. The study showed that the average age of the mothers was 24,40 (SD = 3,38) years, level education varied from elementary to senior high school. Through the findings, three main themes have been identified including knowledge of mothers regarding complementary feeding for stunting prevention. Mothers current practice of providing complementary feeding and challenges in providing complementary feeding practices regarding stunting prevention. Findings from the study may provide information for the nurses in increasing the rate of complementary feeding practice to prevent stunting among mothers of children in Indonesia. Future study is needed to identify the factors influencing complementary feeding among the mothers of 6 - 24 months old children in Indonesia.